2021
DOI: 10.5194/acp-2021-801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the potential for simplification in global climate model cloud microphysics

Abstract: Abstract. Cloud properties and their evolution influence Earth's radiative balance. The cloud microphysical (CMP) processes that shape these properties are therefore important to be represented in global climate models. Historically, parameterizations in these models have grown more detailed and complex. However, a simpler formulation of CMP processes may leave the model results mostly unchanged while enabling an easier interpretation of model results and helping to increase process understanding. This study e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Avramov and Harrington (2010) further suggested, based on a model sensitivity experiment, that the phase partitioning of Arctic low‐level MPCs is strongly sensitive to the assumptions on mass‐size, and size‐fall speed relations of ice particles, and thus on the ice habits included in the model. It can then be expected that in addition to cloud lifetime, phase‐partitioning, and organization, precipitation further affects the radiative characteristics of the MPC (Avramov & Harrington, 2010; Eirund et al., 2019; Harrington & Olsson, 2001; Proske et al., 2021; Solomon et al., 2015; Tan & Storelvmo, 2019). Tan and Storelvmo (2019) have shown that in the Community Earth System Model (CESM) larger ice particles in Arctic MPCs lead to a stronger cloud‐phase feedback, that in turn increases the magnitude of Arctic amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Avramov and Harrington (2010) further suggested, based on a model sensitivity experiment, that the phase partitioning of Arctic low‐level MPCs is strongly sensitive to the assumptions on mass‐size, and size‐fall speed relations of ice particles, and thus on the ice habits included in the model. It can then be expected that in addition to cloud lifetime, phase‐partitioning, and organization, precipitation further affects the radiative characteristics of the MPC (Avramov & Harrington, 2010; Eirund et al., 2019; Harrington & Olsson, 2001; Proske et al., 2021; Solomon et al., 2015; Tan & Storelvmo, 2019). Tan and Storelvmo (2019) have shown that in the Community Earth System Model (CESM) larger ice particles in Arctic MPCs lead to a stronger cloud‐phase feedback, that in turn increases the magnitude of Arctic amplification.…”
Section: Introductionmentioning
confidence: 99%
“…The trajectories indicate then that structural differences in ice microphysics are sufficient to generate such a spread in q i . The two‐moment trajectories differ more from one another than the one‐moment ones, perhaps as the addition of uncertain parameters in more sophisticated schemes expands the space of possible cloud states (e.g., Morrison et al., 2020; Proske et al., 2021). Median N i varies by a factor of six between sets of trajectories, and the N i distributions exhibit quite different forms.…”
Section: Resultsmentioning
confidence: 99%
“…Clouds are an integral part of the Earth's radiation budget and global water cycle (Liou, 1986;Luo and Rossow, 2004;Bony et al, 2015;Zhou et al, 2016). Since cloud microphys-ical processes occur at scales that are much smaller than the resolution of commonly used atmospheric models, it remains a significant challenge for atmospheric models to represent cloud-related processes, especially ice-phase cloud microphysical processes (Mitchell et al, 2008;Spichtinger and Gierens, 2009;Wang and Penner, 2010;Erfani and Mitchell, 2016;Paukert et al, 2019;Morrison et al, 2020;Proske et al, 2022). Because it is impossible for commonly used atmospheric models (excluding the ideal model with the recently developed Lagrangian-particle-based scheme) to individually describe cloud particles (e.g., cloud droplets or ice crystals), only the macrostatistical features of cloud particles are represented in cloud microphysics schemes.…”
Section: Introductionmentioning
confidence: 99%